Case Report: FAS spontaneous mutation in a familial hemophagocytic lymphohistiocytosis patient with a complex heterozygous mutation in PRF1 - Ding, Wenwen; Li, Danni; Yu, Qi; Wang, Yuping; Zhang, Lei (Frontiers in Immunology, 2025)
Familial hemophagocytic lymphohistiocytosis type 2 (FHL2), caused by perforin 1 (PRF 1), is a rare and fatal autosomal recessive disorder characterized by a hyperinflammatory syndrome and the accumulation of activated T lymphocytes and histiocytes in the reticuloendothelial system. Autoimmune lymphoproliferative syndrome (ALPS) is an autoimmune disease that typically presents in children with lymphadenopathy, splenomegaly, and cytopenias or lymphomas. We report a case of a 9-year-old boy who was newly diagnosed with FHL, carrying a new type of compound heterozygous mutations (c.305G>T and c.139G>T) in PRF1 and a spontaneous heterozygous mutation in the FAS gene (c.776T>C). He met six of the eight hemophagocytic lymphohistiocytosis (HLH) diagnostic criteria: fever, splenomegaly, cytopenia, hypofibrinogenemia, hemophagocytosis in the bone marrow, and elevated sCD25. He also had a high proportion of CD3+CD4−CD8− T lymphocytes and a spontaneous mutation of FAS, which are features of ALPS. Chemotherapy failed to control the disease, and the child died within 3 months. FAS and PRF1 comutation may have contributed to the adverse outcome in this patient. Notably, hematopoietic stem cell transplantation (HSCT) should be performed early in these patients.